Advertisement Remove all ads

Simplify and Solve the Linear Equation 3(5z – 7) – 2(9z – 11) = 4(8z – 13) – 17 - Mathematics

Simplify and solve the linear equation 3(5z – 7) – 2(9z – 11) = 4(8z – 13) – 17

Advertisement Remove all ads

Solution

3(5z − 7) − 2(9z − 11) = 4(8z − 13)−17

⇒ 15z − 21 − 18z + 22 = 32z − 52 − 17 (Opening the brackets)

⇒ −3z + 1 = 32z − 69

⇒ −3z − 32z = −69 − 1

⇒ −35z = −70

⇒ `z = 70/35 = 2`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 8 Maths Textbook
Chapter 2 Linear Equations in One Variable
Exercise 2.5 | Q 9 | Page 34
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×